Efficient bioconversion from acid hydrolysate of waste oleaginous yeast biomass after microbial oil extraction to bacterial cellulose by Komagataeibacter xylinus. Issue 10 (26th November 2017) - Luo, Mu-Tan; Huang, Chao; Chen, Xue-Fang; Huang, Qian-Lin; Qi, Gao-Xiang; Tian, Lan-Lan; Xiong, Lian; Li, Hai-Long; Chen, Xin-De
ABSTRACT: Biomass acid hydrolysate of oleaginous yeast Trichosporon cutaneum after microbial oil extraction was applied as substrate for bacterial cellulose (BC) production by Komagataeibacter xylinus (also named as Gluconacetobacter xylinus previously) for the first time. BC was synthesized in static culture for 10 days, and the maximum BC yield (2.9 g/L) was got at the 4th day of fermentation. Most carbon sources in the substrate (glucose, mannose, formic acid, acetic acid) can be utilized by K. xylinus . The highest chemical oxygen demand (COD) removal (40.7 ± 3.0%) was obtained at the 6th day of fermentation, and then the COD increased possibly due to the degradation of BC. The highest BC yield on COD consumption was 38.7 ± 4.0% (w/w), suggesting that this is one efficient bioconversion for BC production. The BC structure was affected little by the substrate by comparison with that generated in classical HS medium using field-emission scanning electron microscope (FE-SEM), Fourier transform infrared, and X-ray diffraction. Overall, this technology can both solve the issue of waste oleaginous yeast biomass and produce valuable biopolymer (BC).